Janus Ga2SeTe and In2SeTe nanosheets: Excellent photocatalysts for hydrogen production under neutral pH. (19th May 2023) - Bouziani, Ilyas; Essaoudi, Ismail; Ainane, Abdelmajid; Ahuja, Rajeev
Abstract: In the past few years, Janus nanosheets have attracted much interest according to their specific structure and considerable potential to address the energy and environmental issues. Herein, the electronic, optical and photocatalytic properties of two-dimensional Janus Ga2 SeTe and In2 SeTe have been studied using ab-initio computations based on the density functional theory. The obtained results show that these nanomaterials exhibit a semiconductor behavior with direct and moderate bandgaps using hybrid HSE06 functional. Subsequently, the understudied compounds present suitable optical conductivity, absorption, transmission and reflectivity for water splitting under the ultraviolet–visible light irradiation. Interestingly, the band edge positions of Janus Ga2 SeTe and In2 SeTe excellently straddle the redox potentials of water under neutral pH. Additionally, the free energy values for the formation of H2 from H adsorbed on the Ga2 SeTe and In2 SeTe compounds are respectively 1.304eV and 0.976eV at pH = 7. More excitingly, the present study proposes strain engineering approach to improve the photocatalytic performance of the Janus Ga2 SeTe and In2 SeTe monolayers. Specifically, the investigated semiconductors show more appropriate band edge alignment and better hydrogen evolution reaction activity under biaxial tensile strain, which fulfil the water splitting requirements at neutral pH conditions. Our findings conclude that the Janus Ga2 SeTe and In2 SeTe nanosheets are promising candidates for photocatalytic hydrogen production. Graphical abstract: Image 1 Highlights: 2D Ga2 SeTe and In2 SeTe semiconductors show direct and moderate bandgaps. They exhibit high light absorption ability in the UV–visible range. Their band edge positions straddle the redox potentials of water at pH = 7. These monolayers provide high HER activity under neutral pH. The present Janus show optimal photocatalytic performance under strain.